Associations of maternal organophosphate pesticide exposure and PON1 activity with birth outcomes in SAWASDEE birth cohort, Thailand - Warangkana Naksen (2018)
© 2015 Elsevier Inc. Prenatal organophosphate (OP) pesticide exposure has been reported to be associated with adverse birth outcomes and neurodevelopment. However, the mechanisms of toxicity of OP pesticides on human fetal development have not yet been elucidated. Our pilot study birth cohort, the Study of Asian Women and Offspring's Development and Environmental Exposures (SAWASDEE cohort) aimed to evaluate environmental chemical exposures and their relation to birth outcomes and infant neurodevelopment in 52 pregnant farmworkers in Fang district, Chiang Mai province, Thailand. A large array of data was collected multiple times during pregnancy including approximately monthly urine samples for evaluation of pesticide exposure, three blood samples for pesticide-related enzyme measurements and questionnaire data. This study investigated the changes in maternal acetylcholinesterase (AChE) and paraoxonase 1 (PON1) activities and their relation to urinary diakylphosphates (DAPs), class-related metabolites of OP pesticides, during pregnancy. Maternal AChE, butyrylcholinesterase (BChE) and PON1 activities were measured three times during pregnancy and urinary DAP concentrations were measured, on average, 8 times from enrollment during pregnancy until delivery. Among the individuals in the group with low maternal PON1 activity (n=23), newborn head circumference was negatively correlated with log10maternal ∑DEAP and ∑DAP at enrollment (gestational age=12±3 weeks; β=-1.0cm, p=0.03 and β=-1.8cm, p<0.01, respectively) and at 32 weeks pregnancy (β=-1.1cm, p=0.04 and β=-2.6cm, p=0.01, respectively). Furthermore, among these mothers, newborn birthweight was also negatively associated with log10maternal ∑DEAP and ∑DAP at enrollment (β=-219.7g, p=0.05 and β=-371.3g, p=0.02, respectively). Associations between maternal DAP levels and newborn outcomes were not observed in the group of participants with high maternal PON1 activity. Our results support previous findings from US birth cohort studies. This is the first study to report the associations between prenatal OP pesticide exposure and birth outcomes in Thailand.